Uma poética do escrever e da escrita em Água viva, de Clarice Lispector - Guarizo, Adriana Monteiro Piromali [UNESP] (2013)
This work investigates a fundamental element in the work of Clarice Lispector that addresses the relations between the subject of language and that of writing, as well as their implications. To do that, it studies the way these relations are established in some of her novels, short stories, chronicles and ultimately Água viva. Água viva follows two approaches to writing. On the one hand, it tends to abide by the conventions of genre, which are also conventions of criticism, reading, and even of the market. All in all, books have to be sold. On the other hand, it tends to subvert these conventions by innovating and surpassing the exigencies of genre, criticism, reading and market, for art also lives upon resisting such demands. Hence we believe that Água viva is at the very heart of a reflection and/or constitutes the culmination of the thematic and formal debate concerning Clarice’s main poetic principle, which is encapsulated in the title of this work – “A poetics of writing in Água viva”. Due to that, we had to tackle Clarice’s literary project as being marked by the tension between the writing of literature and writing as such in that Água viva epitomizes the prevalence of latter over the former due to the literary project and procedures this work studies. Therefore, the reading of Água viva sheds light on Clarice’s fragmentary reflections which are to be found in other texts of hers as well. These fragments reveal an author caught between the writer and that who writes, the one who discusses her craft with her reader and invites them to participate in her text and to partake her passion for writing